Exploring Quality of Life and Caregiver Burden in Palliative care - Srivastava , Kajal; Rathod, Hetal; Bhawalkar , Jitendra Shyamsundar; Vishwakarma, Kavitha Satyendra; R, AKHIL (Indian Journal of Community Health, 2025)
Background: The increasing prevalence of non-communicable diseases in India has led to a growing need for palliative care. This study aimed to explore and analyse the factors contributing to the quality of life and burden experienced by caregivers of palliative patients in a metropolitan setting. Methodology: A qualitative phenomenological approach was employed, grounded in the interpretivist paradigm. Seven in-depth, semi-structured interviews were conducted with primary caregivers of palliative patients at a tertiary care hospital and Palliative Care Hospital. Purposive sampling was used, and data saturation determined the sample size. Interviews were audio-recorded, transcribed, and translated. Data analysis followed a hybrid approach, combining inductive and deductive methods. Results: Seven major themes emerged from the analysis. Caregivers reported significant deterioration in their quality of life, disruption of daily routines, and emotional distress. They faced challenges including physical and mental exhaustion, lack of respite, and financial constraints. Coping mechanisms included seeking emotional support and spiritual practices. Despite hardships, caregivers found satisfaction in witnessing improvements in their loved ones' conditions. They expressed concerns about future care arrangements and suggested better communication with healthcare professionals and respite opportunities. Conclusion: The study revealed that caregiving for palliative patients significantly impacts caregivers' quality of life and emotional well-being. While caregivers experience multiple challenges, they also find satisfaction in their role. To improve the caregiving experience, healthcare systems should focus on enhancing communication between healthcare professionals and patients, and providing respite options for caregivers. These findings can inform strategies to support caregivers and improve palliative care services in metropolitan settings.